若a=2003,b=2004,c=2005,求a∧2+b∧2+c∧2-ab-ac-bc
1个回答
a^2+b^+c^2-ab-ac-bc
=[(a-b)^2+(b-c)^2+(c-a)^2]/2
=(1+1+2^2)/2
=3
相关问题
若a=2003,b=2004,c=2005,求a^2+b^2+c^2-ab-bc-ac的值.
若a=2003,b=2004,c=2005,求a2+b2+c2-ab-bc-ac的值.
若a=2003,b=2004,c=2005,求a2+b2+c2-ab-bc-ac的值.
a=-2006,b=2005,c=-2004求a^2+b^2+c^2+ab+bc+-ac
a=-2004 b=2003 c=-2002 a^2+b^2+c^2+ab+bc-ac
完全平方公式a=-2004 b=2003 c=-2002求a2+b2+c2+ab+bc-ac
已知a=2002,b=2003,c=2004,求a^2+b^2+c^2-ab-ac-bc的值
若a=2003,b=2004,c=2005,求a+b+c-ab-bc-ac的值.(写出化简的过程)
已知a=2004x-2001,b=2004x-2002,c=2004x-2003,求a2+b2+c2-ab-ac-bc的
若a+x^2=2004,b+x^2=2005,c+x^2=2006,且abc=12,求a/bc+b/ac+c/ab-1/